2014
DOI: 10.15740/has/tajas/9.2/129-133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walnut powder incorporation on sensorial, nutritional and textural quality profile of Burfi

Abstract: ABSTRACT...... In present investigation Burfi was prepared from buffalo milk with constant level of sugar (30 % by weight of Khoa) and different levels of walnut powder (2, 4, 6 and 8 % by weight of Khoa). It was observed that the overall acceptability score for treatment T 1 , T 2 , T 3 , T 4 and T 5 were 8. 76, 8.45, 8.16, 7.80 and 7.50, respectively. The results revealed that as the level of walnut powder in Burfi increases the overall acceptability score decreases. On the basis of results it could be conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…This may be due to the lower moisture content of ber powder. The result here is in agreement with walnut powder burfi (Satav et al 2014). Similar findings were reported byJha et al(2014) in lalpeda.…”
Section: Instrumental Texture Parameterssupporting
confidence: 93%
“…This may be due to the lower moisture content of ber powder. The result here is in agreement with walnut powder burfi (Satav et al 2014). Similar findings were reported byJha et al(2014) in lalpeda.…”
Section: Instrumental Texture Parameterssupporting
confidence: 93%
“…It was predicted from the sensory score of basundi with red pumpkin pulp that treatment T 0 , T 1 , T 2 and T 3 differ significantly for these sensory parameters. The result was in confirmation with Waghmare (2012) and Satav (2014) who reported significance effect of addition of bottle gourd pulp and walnut powder on the overall acceptability of burfi.…”
Section: Overall Acceptabilitysupporting
confidence: 84%
“…The total solids increased in both the treatments may be due to the proportionate reduction in moisture at different storage temperature levels. Shete et al [7] reported that total solids content in burfi was increased from 74.13 to 82.90%, Chavhan [8] and Satav et al [9] also found same treatment results. These results are in agreement with present results found in experimental trial.…”
Section: Total Solidsmentioning
confidence: 84%